Explaining differences in environmental policy across Europe: the importance of informal institutions, incomplete information and path dependence - Frank Wätzold (UFZ-Umweltforschungszentrum Leipzig-Halle, 2006)
What factors shape environmental policies across Europe? In order to answer this question most economists would probably adopt a Public Choice approach. This approach has explained some aspects of environmental policies that exist in a similar fashion across Europe convincingly. But why do many environmental policies differ across European countries? This article argues that in order to understand differences in environmental policies in Europe North's analysis on institutions and institutional change is useful. It demonstrates the relevance of North's approach with a case study: the implementation of the EU's Eco- Management and Audit Scheme in Germany, the Netherlands and the UK. The starting point of the analysis is the observation that participation of companies in the scheme markedly differs between countries. It is shown that in order to understand these differences it is necessary to take into account some key concepts of North's institutional analysis, namely, differences in informal institutions, incomplete information of relevant actors, and path dependence. Recommendations for further research and for environmental policy are derived.
Keywords: 330; Environmental policy; informal institutions; incomplete information; path dependence; European policy; environmental management; Umweltpolitik; Öko-Audit; EU-Umweltpolitik; Einführung; Institutioneller Wandel; Vergleich; Deutschland; Niederlande; Großbritannien